Pemanfaatan Potensi Limbah Industri Pengolahan Ikan Patin (Pangasius Sp) Di Kabupaten Kampar - iqbal, imam; Riza, Subkhan; Gevisioner; Utiya Syah, Shinta; Muhammad Ilham, Andi; Mastina, Tien (Badan Riset dan Inovasi Daerah (BRIDA) Provinsi Riau, 2023)
Patin processing industry produces waste in the form of bones, heads, entrails and skin. Waste from the catfish processing industry in Kampar Regency has not been widely used by the community. Generally, processed waste is immediately thrown away or buried in the ground because there is no commercial utilization effort. This research aims to calculate the potential and utilization of waste from patin fish (Pangasius sp) processing industry in Kampar Regency. This research uses a descriptive research approach. Data analysis was carried out descriptively referring to research results and other related references. The potential for catfish skin waste produced from the fish fillet processing industry in Kampar Regency is 11.98 kg/month. Catfish skin can be processed into gelatin. The potential waste of catfish bones and heads originating from the catfish fillet processing industry is 142.76 kg/month. Patin bones can be processed into fish bone meal and gelatin. The potential for catfish innards from the smoked catfish processing business in Kampar Regency is 20,693.49 kg every month. Catfish viscera and abdominal fat waste can be processed into fish oil, biodiesel, fish meal, fertilizer and animal feed.